2013
DOI: 10.1075/eww.34.1.01seo
|View full text |Cite
|
Sign up to set email alerts
|

The expression of the perfect in East and South-East Asian Englishes

Abstract: This paper looks at variation in the expression of perfect meaning in Asian Englishes (Hong Kong, India, Singapore and the Philippines) as represented in the spoken component of theInternational Corpus of English. Findings confirm the existence of levelling between the present perfect and simple past in these varieties, and that the tendency of the present perfect to lose ground to the preterite is more pronounced in these New Englishes than in British English, especially in the expression of recent past. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…For Werner (, ), the key to unravelling the perfect system rests with the relative specificity of temporal adverbs against which present and past tense and present perfect uses are then related and can be measured. For Seoane and Suárez‐Gómez () the key is unravelling the set of semantic functions of the perfective and comparing their realisation between present perfects and the present and past tenses. As Table shows, this approach has considerable merit, for it regards each perfective type as a variable, so that one proceeds from meaning to expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For Werner (, ), the key to unravelling the perfect system rests with the relative specificity of temporal adverbs against which present and past tense and present perfect uses are then related and can be measured. For Seoane and Suárez‐Gómez () the key is unravelling the set of semantic functions of the perfective and comparing their realisation between present perfects and the present and past tenses. As Table shows, this approach has considerable merit, for it regards each perfective type as a variable, so that one proceeds from meaning to expression.…”
Section: Discussionmentioning
confidence: 99%
“…The first semantic function expresses a ‘state leading up to the present’ (Quirk et al. : 192), ‘a state‐up‐to‐the‐present’ (Leech : 36–37), an ‘extended now’ sense (Hickey : 196), a ‘continuative’ (as opposed to the others being ‘non‐continuative’) time frame (Comrie 1976; Huddleston : 141; van Rooy ), and a ‘persistent situation’ (Seoane & Suárez‐Gómez ). For McCawley () and Kallen (: 123) it is a ‘universal perfect’ for its meaning relates to a state of affairs continuing without a break ever since an event in the past occurred, equating it with the Irish uses of the ‘extended now’ or ‘extended present’ tense (Kallen : 123).…”
Section: The Present Perfect Construction In Ice‐irelandmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now evident that many new varieties of English share non‐standard morpho‐syntactic forms and that this therefore questions the essential role of the second language (Deterding & Kirkpatrick ; Mesthrie ). In a recent study on the use of the perfect in East and Southeast Asian Englishes, as illustrated in the spoken sections of four corpora of the International Corpus of English, namely Hong Kong, India, Singapore and the Philippines (Seoane & Suarez‐Gomes ), the authors’ findings indicate that there is a levelling in the use of the present perfect and the simple past in these Asian varieties of English, and that this levelling is also reflected in contemporary British English. It is also a well‐known feature of American English.…”
Section: Language Contact – Non‐standard Forms and Code‐mixingmentioning
confidence: 95%
“…7 The size of ICE, one million words per variety, may be considered small by comparison with current standards (see BNC, with 100 million words, COCA, with 520 million words, etc.). Yet it is sufficient for the study of grammatical variation, as shown by Seoane and Suárez-Gómez's (2013) study of the perfect meaning in Asian varieties, by Suárez-Gómez (2014), which analyses relative clauses, and by Loureiro-Porto (2016), which focuses on modal verbs. However, if the aim is to study low frequency items, such as lexical elements, specific collocations or contractions and even syntactic constructions (e.g., García-Castro 2017), ICE's size is clearly one of its main disadvantages.…”
Section: The Ice Projectmentioning
confidence: 99%